Optimization Media for the Growth of Chlorella vulgaris in Co-Culture with Bacteria - Sitoresmi Prabaningtyas; Fairus Zain; Dila Amelia; Raden Roro Ranty Kusumaningayu; Dhiyauddin Aridhowi; Achmad Rodiansyah; Ida Mawadah; Dita Ayu Eka Saputri (Sam Ratulangi University, 2025)
The demand for fuel energy in Indonesia is continuously rising, while the availability of fossil fuels is increasingly limited. Consequently, an alternative renewable biodiesel feedstock, such as the microalga Chlorella vulgaris, is urgently needed. One effective strategy to boost microalgal biomass is through co-culture with bacteria, as the positive interactions between the two have been proven to accelerate microalgal growth rates via various mechanisms. As an essential factor in the cultivation process, the selection of a culture medium that provides optimal nutrition is a crucial step to support maximum C. vulgaris growth. This study, therefore, aims to evaluate the optimization of both the culture medium and the bacterial co-culture technique to maximize C. vulgaris proliferation. We compared the effectiveness of two culture media (Gusrina Medium and Guillard Medium) and two levels of bacterial addition (monoculture and co-culture). Cultivation was performed in a photobioreactor with a 12-hour on : 12-hour off aeration cycle and a 16-hour light : 8-hour dark photoperiod. The results demonstrate that microalgae-bacteria co-culture in Gusrina Medium yielded the most optimal C. vulgaris cell growth. The best bacterial combination utilized in the co-culture consisted of IAA (Indole Acetic Acid) producing bacteria, phosphate-solubilizing bacteria, and amylolytic bacteria. This specific combination of medium and bacteria is recommended for the large-scale development of C. vulgaris biomass as a sustainable biodiesel feedstock.